2018
DOI: 10.1002/ejhf.1053
|View full text |Cite
|
Sign up to set email alerts
|

Daily home BNP monitoring in heart failure for prediction of impending clinical deterioration: results from the HOME HF study

Abstract: The HOME HF study demonstrates the feasibility of home BNP measurement and shows the potential value of fBNP as an index of emerging clinical deterioration. Assessment of the clinical value of this is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 22 publications
(29 reference statements)
2
30
0
1
Order By: Relevance
“…Main results of two trials are shown: the Double‐blind, RandOmised, two‐arm Parallel group, serum c‐terminal Propeptide of Procollagen type I (DROP‐PIP) trial and the Heart Failure Outpatient Monitoring Evaluation (HOME HF) study …”
Section: Main Results Of Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Main results of two trials are shown: the Double‐blind, RandOmised, two‐arm Parallel group, serum c‐terminal Propeptide of Procollagen type I (DROP‐PIP) trial and the Heart Failure Outpatient Monitoring Evaluation (HOME HF) study …”
Section: Main Results Of Clinical Trialsmentioning
confidence: 99%
“…HOME HF was designed as a randomized clinical trial to test the hypothesis that daily brain natriuretic peptide (BNP) measurements at home could improve outcomes, compared to a home management system without BNP measurements or routine clinical care, in patients with HF and reduced ejection fraction (HFrEF) . The study was terminated early because of slow enrolment and the need for an algorithm testing serial BNP changes.…”
Section: Main Results Of Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…102 Neutral results may be caused by both the type of the intervention and patients selection. 104 Telemedical Interventional Management in HF II (TIM-HF2) was a randomized, controlled trial investigating the impact of telemedicine on unplanned cardiovascular hospitalizations and mortality in HF patients. 103 Nurse home visits had also the greatest pooled cost savings.…”
Section: Telemedicinementioning
confidence: 99%
“…Although the trial showed the feasibility of this approach, it was terminated early because of slow enrolment, low event rates, and the need of an algorithm taking care of spontaneous BNP fluctuations. 104 Telemedical Interventional Management in HF II (TIM-HF2) was a randomized, controlled trial investigating the impact of telemedicine on unplanned cardiovascular hospitalizations and mortality in HF patients. Study patients were selected based on the analysis of the previous TIM-HF trial, which was neutral.…”
Section: Telemedicinementioning
confidence: 99%